Looking Back to Look Ahead: COVID-19, domestic violence, and digital activism in India - Mukherjee, Ishani; Williams, Maggie G.; Sen, Soham (Frontiers in Communication, 2024)
We look back to explore the impact of COVID-19 lockdowns on domestic violence amplification in India and the digital activisms that spotlighted this social and health injustice. This analysis focuses on two case studiesthe #LockDownMeinLockUp [#LDMLU] campaign mobilized on Instagram in 2020, and articles drawn from the digital feminist publication, Feminism in India [FII]. We share our perspectives on how the #LDMLU campaign visually politicized the public nature of a silenced and normalized injustice against at-risk women during a pan-national health crisis. We turn to FII's reporting on DV exacerbation during India's pandemic that vocalized this issue from three critical perspectives: structural problems that contribute to gender injustices; financial violence; and mental, emotional, and physical health impacts on abused and at-risk women. In addition to this 'look back,' we look ahead to consider calls-to-action and opportunities, digital and/or on-ground, that remain imperative after the urgency of the viral lockdown. We are still at the threshold of activisms waiting, and needing, to happen. We conclude with questions for ourselves and our readers about what happens to advocacy when urgency ends. This growing body of feminist work demonstrates that advocacy will persist across physical and virtual landscapes. It is our responsibility and hope, as gender and communication scholars, to rally challenges against oppression based on gender or sex. Domestic violence against Indian women is continually overlooked. Our collective perspective intends to consolidate visibility toward such acts of abuse at the center of this scholarly piece.